INSTILLING ENVIRONMENTAL AWARENESS AND NATURALISTIC INTELLIGENCE IN EARLY CHILDHOOD EDUCATION: A CASE STUDY OF A KINDERGARTEN IN INDONESIA - Kamil, Nurhusni (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
Children should be exposed to character education at an early age. Naturalistic intelligence and environmental consciousness should be introduced and instilled early on. The 2013 Curriculum includes this love of nature as one of the components of religious and moral growth. In spiritual and ethical development, we learn about the value and respect for God’s creations as well as appropriate behavior toward other living beings, including plants and animals. The loving-nature mindset is integrated into the learning objectives of religious values and character in the Independent Curriculum (Kurikulum Merdeka). This study aims to describe the forms of nature-loving education in a kindergarten in Indonesia and the types of activities that children can engage in. This research employs a qualitative methodology with a case study approach. The population of this study consists of all 18 children in Kindergarten B. Data collection was conducted using observation and checklist assessment techniques, and data analysis followed the Miles and Huberman technique. The results indicate that children are more enthusiastic about visiting animal enclosures directly and creating crafts from recycled materials as part of fostering naturalistic intelligence and a love for nature.